Pain management in eldercare employees - the role of managers in addressing musculoskeletal pain and pain-related sickness absence - Charlotte Diana Nørregaard Rasmussen; Jodi Oakman; Kristina Karstad; Reiner Rugulies; Andreas Holtermann; Matthew Leigh Stevens (BMC, 2022)
Abstract Purpose Managers' knowledge and behaviors in addressing musculoskeletal pain and sickness absence is not well understood. We investigated the association between managers' knowledge and behaviours in relation to employees' pain and their future risk of musculoskeletal pain and associated sickness absence. Methods The prospective study included 535 eldercare employees, and 42 managers from 20 nursing homes. Managers' self-reported knowledge and behaviors in relation to employees' pain were grouped using Principal Components Analysis. Eldercare employees reported pain-related sickness absence, and number of days with musculoskeletal pain repeatedly over 1 year. We investigated associations using mixed-effects regression models. Results We identified four types of managers' knowledge and behaviors: 1) Pain-prevention (actions for prevention of employee pain), 2) Pain-management (actions to assist employees manage pain), 3) Pain-entitlements (communicating entitlements to employees with pain), and 4) Pain-accommodations (ability to facilitate workplace accommodations for employees with pain). The employees of managers with higher scores on knowledge of pain-entitlements reported fewer days of pain-related sickness absence (β = -0.62; 95%CI [-1.14; -0.10]). The employees of managers with higher scores on pain-management were more likely to report low back pain (β = 0.57; 95%CI [0.02; 1.11]). We found several key associations between the knowledge and behaviors measures and pain-related sickness absence (interactions). Conclusion Managers' knowledge and behaviors in relation to employees' pain were associated with employees' future musculoskeletal pain and sickness absence. The relationships are complex, suggesting that a multifaceted approach is needed to ensure that managers are adequately informed on how to manage and accommodate employees with musculoskeletal pain to reduce sickness absence.